PBAT / PLA sheath-core composite fiber, preparation method thereof and hygienic product

By modifying PLA and PBAT to form furated PLA and anhydride PBAT, and spinning, the poor compatibility problem in the preparation of PBAT/PLA leather core composite fibers is solved, and the preparation of composite fibers with high strength and long-term capacity is achieved.

CN119753887AActive Publication Date: 2025-04-04WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411949299.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In the prior art, PBAT and PLA have poor compatibility in the preparation process of PBAT/PLA leather core composite fiber, resulting in low strength and poor toughening effect of blended materials.

Method used

The PLA and PBAT were modified by using an ester group-containing furan derivative and an ester group-containing acid anhydride derivative to form a furanized PLA and anhydride PBAT, followed by spinning to achieve the preparation of the skin-core composite fiber.

Benefits of technology

It effectively improves the compatibility between PBAT and PLA, improves the strength and toughening performance of composite fibers, improves the rapid compatibility between the cortex and core layer during spinning, is suitable for industrial continuous production, and achieves long-term capacity enhancement effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753887A_ABST
    Figure CN119753887A_ABST
Patent Text Reader

Abstract

The invention discloses a PBAT / PLA sheath-core composite fiber, a preparation method thereof and a hygienic product, belongs to the technical field of PBAT / PLA sheath-core composite fibers, and solves the problem of poor compatibility of PBAT and PLA in the preparation process of the PBAT / PLA sheath-core composite fiber in the prior art. The preparation method of the PBAT / PLA sheath-core composite fiber comprises the following steps: S1, modifying PLA by adopting one of an ester group-containing furan derivative and an ester group-containing anhydride derivative to obtain modified PLA; the preparation method comprises the following steps: modifying PBAT by adopting the other one of an ester group-containing furan derivative and an ester group-containing anhydride derivative to obtain modified PBAT; and S2, carrying out spinning by adopting the modified PLA and the modified PBAT. The skin layer and the core layer of the skin-core composite fiber prepared by the invention are increased in capacity for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PBAT / PLA sheath-core composite fibers, and in particular relates to a PBAT / PLA sheath-core composite fiber and a preparation method thereof and sanitary products. Background Art

[0002] With the improvement of people's living standards, sanitary materials have entered the fourth generation, that is, the pursuit of easier, softer and more comfortable direction. Especially in baby diapers and disposable sanitary products, high-grade hot air non-woven fabrics made of ES (Ethylene-Propylene SideBy Side) fiber have become the main raw materials. ES fiber is a sheath-core composite fiber composed of two different polymer materials, with good softness, low melting point of the outer layer, high melting point of the inner layer, and high strength. After reprocessing heat treatment, part of the cortex is melted and bonded, and the remaining fibers remain in the fiber state, which not only maintains the fluffy and soft characteristics of the fiber, but also does not destroy the structure of the fiber. It has high strength and is particularly suitable for the production of sanitary materials, thermal insulation fillers, filter materials and other products. At present, the ES fibers on the market are mainly PE / PP composite fibers and PE / PET composite fibers. Due to the poor biodegradability of these materials, they will cause non-negligible pollution to the environment after being discarded. Therefore, the research and development of ES fibers based on biodegradable materials and disposable sanitary products are of great significance to environmental protection and the development of green sustainable economy.

[0003] Poly(butylene terephthalate-co-ethylene terephthalate) (PBAT for short) has become a type of biodegradable plastic component that is currently being focused on because of its excellent toughness and fatigue resistance, high impact strength, and excellent biodegradability. In addition, polylactic acid (PLA for short) has the advantages of good biodegradability, high mechanical strength, and simple processing. It can be produced and prepared using resources such as biomass starch. It is an ideal bio-based degradable engineering plastic. In order to make up for the brittleness defect of PLA, flexible PBAT is usually introduced to improve the toughness of the material. Although the performance of the two materials can be complementary, it was found during use that due to the large structural differences between the two materials, the compatibility of the two after blending is poor, which greatly reduces the strength of the blended material and reduces the toughening effect, resulting in the performance of the blended material being lower than expected.

[0004] In order to improve the interaction between PLA and PBAT, the compatibility of the blend can be improved by a modification method, thereby improving the comprehensive performance of the material. The main methods of increasing the capacity currently used include adding inorganic materials, chain extenders, compatibilizers, natural polymer compounds, and nanomaterial modifications. However, from the perspective of the processing and molding of PBAT / PLA core-skin composite fibers, the above method will have a greater impact on spinnability. Specifically, since the two plastics are melt-extruded by a single-screw extruder during the spinning process and then transported to the spinning assembly by a metering pump, the two melts are combined at the spinneret of the composite spinning assembly and then ejected through the spinneret hole, and then wound at a certain spinning speed. Therefore, the reaction time of the two melts at the spinneret hole using the above modification method is short, and efficient and rapid volume increase reaction cannot occur. In addition, using the above modification method of adding substances, a new interface layer is prone to appear and defects are prone to occur, further reducing the spinnability and winding speed of the ES fiber.

[0005] In summary, with regard to the compatibility issues of ES fibers mentioned above, the existing technology cannot achieve rapid capacity expansion of PBAT / PLA sheath-core composite fibers. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the problem of poor compatibility between PBAT and PLA in the preparation process of PBAT / PLA sheath-core composite fibers in the prior art, thereby providing a PBAT / PLA sheath-core composite fiber and a preparation method thereof and a sanitary product.

[0007] To this end, the present invention provides the following technical solutions.

[0008] In a first aspect, the present invention provides a method for preparing a PBAT / PLA sheath-core composite fiber, comprising:

[0009] S1, modifying PLA using one of an ester-containing furan derivative and an ester-containing anhydride derivative to obtain modified PLA;

[0010] Modifying PBAT with the other of an ester-containing furan derivative and an ester-containing anhydride derivative to obtain a modified PBAT;

[0011] S2. Using the modified PLA and the modified PBAT to perform spinning.

[0012] In one possible embodiment, S1, PLA is modified with an ester-containing furan derivative to form furanized PLA;

[0013] Modifying PBAT with an anhydride derivative containing an ester group to form an anhydride PBAT;

[0014] S2. Spinning the furanized PLA and the anhydride-treated PBAT.

[0015] In one possible embodiment, S1, PLA is modified with an anhydride derivative containing an ester group to form anhydride PLA;

[0016] The PBAT is modified with a furan derivative containing an ester group to form a furanized PBAT;

[0017] S2. Spinning the anhydride-treated PLA and the furanized PBAT.

[0018] In a possible embodiment, the step of modifying PLA by using one of an ester-containing furan derivative and an ester-containing acid anhydride derivative to obtain modified PLA comprises: subjecting the ester-containing furan derivative or the ester-containing acid anhydride derivative to an ester exchange reaction with the PLA;

[0019] Preferably, the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA are first melt-blended;

[0020] Preferably, the molar ratio of the ester-containing furan derivative or the ester-containing anhydride derivative to the PLA is (2-8): (8-2);

[0021] Preferably, the conditions of the first melt blending include: blending time of 10 min-45 min, temperature of 150° C.-210° C.; further, screw speed of 60 r / min-100 r / min;

[0022] Preferably, before the first melt blending, the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA are dried respectively;

[0023] Preferably, the drying conditions for drying the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

[0024] In a possible embodiment, the structural formula of the ester-containing furan derivative is as follows:

[0025] Among them, R 1 is selected from substituted or unsubstituted aromatic groups or substituted or unsubstituted alkylene chains, R 2 is a substituted or unsubstituted alkylene chain;

[0026] Preferably, R 1 is selected from substituted or unsubstituted phenyl or substituted or unsubstituted C1-C10 alkylene chain, R 2is a substituted or unsubstituted C1-C10 alkylene chain;

[0027] Preferably, R 1 is selected from unsubstituted phenyl or unsubstituted C1-C10 alkylene chain, R 2 is an unsubstituted C1-C10 alkylene chain;

[0028] More preferably, R 1 is selected from unsubstituted phenyl or unsubstituted C2-C8 alkylene chains, R 2 is an unsubstituted C2-C8 alkylene chain;

[0029] In a possible embodiment, the structural formula of the ester-containing anhydride derivative is as follows:

[0030] Among them, R 3 is selected from a substituted or unsubstituted aromatic group or a substituted or unsubstituted alkylene chain;

[0031] R 3 Preferred is a substituted or unsubstituted phenyl group or a substituted or unsubstituted C1-C10 alkylene chain, more preferably an unsubstituted phenyl group or an unsubstituted C1-C10 alkylene chain, and most preferably an unsubstituted phenyl group or an unsubstituted C2-C8 alkylene chain.

[0032] In a possible embodiment, the step of modifying PBAT with the other of an ester-containing furan derivative and an ester-containing acid anhydride derivative to obtain modified PBAT comprises: subjecting the ester-containing acid anhydride derivative or the ester-containing furan derivative to an ester exchange reaction with PBAT;

[0033] Preferably, the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT are subjected to a second melt blending;

[0034] Preferably, the molar ratio of the ester-containing anhydride derivative or the ester-containing furan derivative to the PBAT is (2-8): (8-2);

[0035] Preferably, the conditions of the second melt blending include: blending time of 10 min-45 min, temperature of 150° C.-210° C.; further, screw speed of 60 r / min-100 r / min;

[0036] Preferably, before the second melt blending, the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT are dried respectively;

[0037] Preferably, the conditions for drying the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

[0038] In a possible implementation, the core layer raw material for forming the core layer of the PBAT / PLA sheath-core composite fiber includes the modified PLA;

[0039] The raw material for forming the skin layer of the PBAT / PLA skin-core composite fiber includes the modified PBAT;

[0040] Spinning is performed according to a two-component spinning process;

[0041] Preferably, in the two-component spinning process, the skin layer melt extrusion temperature is 190°C-220°C, and the core layer melt extrusion temperature is 195°C-220°C; the number of spinneret holes is 36-100, the spinning temperature is 195°C-210°C, and the spinning speed is 500m / min-3000m / min.

[0042] In a possible implementation manner, the core layer raw material further includes PLA, and the amount of the modified PLA is 2%-20% of the mass of the PLA;

[0043] Preferably, the skin layer raw material further comprises PBAT, and the amount of the modified PBAT is 2%-20% of the mass of the PBAT;

[0044] Preferably, the mass ratio of the core layer raw material to the skin layer raw material is (3:7)-(7:3);

[0045] Preferably, before spinning, the core layer raw material and the skin layer raw material are dried separately;

[0046] Preferably, the conditions for drying the core layer raw material and the skin layer raw material respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

[0047] In a second aspect, the present invention provides a PBAT / PLA sheath-core composite fiber, which is prepared by the preparation method of the PBAT / PLA sheath-core composite fiber.

[0048] In a third aspect, the present invention provides a sanitary product comprising the PBAT / PLA sheath-core composite fiber.

[0049] The technical solution of the present invention has the following advantages:

[0050] 1. The preparation method of the PBAT / PLA sheath-core composite fiber of the present invention comprises: S1, using one of an ester-containing furan derivative and an ester-containing acid anhydride derivative to modify PLA to obtain modified PLA; using the other of an ester-containing furan derivative and an ester-containing acid anhydride derivative to modify PBAT to obtain modified PBAT; S2, using the modified PLA and the modified PBAT for spinning.

[0051] The present invention adopts modified PLA and modified PBAT to prepare PBAT / PLA sheath-core composite fiber. When PLA is modified by ester-based furan derivatives, PBAT is modified by ester-based anhydride derivatives; when PLA is modified by ester-based anhydride derivatives, PBAT is modified by ester-based furan derivatives. The temperature-induced DA reaction between the diene on the furanized PLA and the monoene on the anhydride PBAT occurs during the spinning process, or the temperature-induced DA reaction between the diene on the furanized PBAT and the monoene on the anhydride PLA occurs during the spinning process, thereby effectively solving the problem of phase separation caused by poor compatibility of PBAT and PLA segments; effectively alleviating the peeling between the skin layer and the core layer of the composite fiber during the spinning process, achieving rapid compatibility between the skin layer and the core layer during the melt spinning process, greatly improving the spinnability and spinning speed of the skin-core composite fiber, and facilitating industrial continuous production; at the same time, the skin layer and the core layer of the prepared skin-core composite fiber will not phase separate over time, achieving long-term capacity expansion; achieving the need to add additional fillers and other capacity expanders, effectively avoiding the problems of low spinnability and safety of the capacity expander material during the fiber processing and molding process caused by the residue of the modifier. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 The synthetic route of PLA-FU provided in Examples 1 and 2 of the present invention;

[0054] Figure 2 The synthetic route of PBAT-AA provided in Example 1 and Example 2 of the present invention;

[0055] Figure 3 The reaction equation for the interfacial compatibilization of the PBAT / PLA sheath-core composite fiber provided in Examples 1 and 2 of the present invention;

[0056] Figure 4The optical microscope morphology of the PBAT / PLA sheath-core composite fibers provided in Examples 1 to 3 of the present invention;

[0057] Figure 5 The scanning electron microscope morphology images of the PBAT / PLA sheath-core composite fibers provided in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0058] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0059] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0060] In a first aspect, the present invention provides a method for preparing a PBAT / PLA sheath-core composite fiber, comprising: modifying PLA using an ester-containing furan derivative (hereinafter referred to as FU) to form furanated PLA (hereinafter referred to as PLA-FU); modifying PBAT using an ester-containing anhydride derivative (hereinafter referred to as AA) to form an anhydride PBAT (hereinafter referred to as PBAT-AA); and spinning the furanated PLA and the anhydride PBAT.

[0061] Among them, PLA-FU includes diene bonds, and PBAT-AA contains monoene bonds. During the spinning process, the monoene undergoes a temperature-induced DA reaction, which enables PLA and PBAT to be fully connected, improving the poor compatibility caused by the large structural differences between the two in the prior art, and the subsequent phase separation problem, and ultimately improving the performance of PBAT / PLA sheath-core composite fibers.

[0062] Specifically, the preparation process is as follows:

[0063] S1, formation of PLA-FU;

[0064] The ester-containing furan derivative and the PLA are subjected to an ester exchange reaction to form PLA-FU. The specific steps include: drying FU and PLA in a vacuum oven at 70°C-100°C for 12h-24h respectively, and then melt-blending the two, for example, using an internal mixer for melt-blending, and the set conditions are: screw speed of 60r / min-100r / min; blending time of 10min-45min, temperature of 150°C-210°C; wherein the molar ratio of FU to PLA is (2-8): (8-2).

[0065] The molar amount of PLA = m 1 / Mw 1 , where m 1 is the mass of PLA, Mw 1 is the weight average molecular weight of PLA.

[0066] The structural formula of the furan derivative containing an ester group is shown below:

[0067] Among them, R 1 is selected from substituted or unsubstituted aromatic groups or substituted or unsubstituted alkylene chains, preferably, R 1 is selected from substituted or unsubstituted phenyl or substituted or unsubstituted C1-C10 alkylene chain, and more preferably R 1 is selected from unsubstituted phenyl or unsubstituted C1-C10 alkylene chains, more preferably R 1 is selected from unsubstituted phenyl or unsubstituted C2-C8 alkylene chains. 1 is phenyl or -(CH 2 ) n -, n is 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0068] R 2 is a substituted or unsubstituted alkylene chain; preferably, R 2 is an unsubstituted C1-C10 alkylene chain; more preferably, R 2 is a substituted or unsubstituted C2-C8 alkylene chain.

[0069] It should be noted that the above-mentioned furan derivative containing an ester group, namely FU, can be any furan containing an ester group, and the furan derivative containing an ester group of the present invention is only an example of the embodiment of the present invention.

[0070] The equipment used for melt blending may be not only an internal mixer but also other equipment in the prior art that can realize melt blending.

[0071] S2, forming PBAT-AA;

[0072] The ester-containing anhydride derivative and PBAT are subjected to an ester exchange reaction. Specifically, the AA and PBAT resins are dried in a vacuum oven at 70°C-100°C for 12h-24h, and the AA and the PBAT are melt-blended; for example, an internal mixer is used for melt blending, and the conditions are set as follows: the screw speed is 60r / min-100r / min; the blending time is 10min-45min, and the temperature is 150°C-210°C; wherein the molar ratio of AA to PBAT is (2-8): (8-2).

[0073] Molar amount of PBAT = m 2 / Mw 2 , where m 2 is the mass of PBAT, Mw 2 is the weight average molecular weight of PBAT.

[0074] The structural formula of the acid anhydride derivative containing an ester group is shown below:

[0075] Among them, R 3 is selected from substituted or unsubstituted aromatic groups or substituted or unsubstituted alkylene chains; preferably substituted or unsubstituted phenyl groups or substituted or unsubstituted C1-C10 alkylene chains, more preferably unsubstituted phenyl groups or unsubstituted C1-C10 alkylene chains, most preferably unsubstituted phenyl groups or unsubstituted C2-C8 alkylene chains.

[0076] For example, R 3 is phenyl or -(CH 2 ) n -, n is 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0077] It should be noted that the above-mentioned acid anhydride derivative containing an ester group, namely AA, can be any acid anhydride containing an ester group, and the acid anhydride derivative containing an ester group of the present invention is only an example of the embodiment of the present invention.

[0078] The equipment used for melt blending may be not only an internal mixer but also other equipment in the prior art that can realize melt blending.

[0079] S3, forming PBAT / PLA skin-core composite fiber;

[0080] PBAT and PBAT-AA are used as raw materials for forming the cortex. Specifically, PBAT and PBAT-AA are physically blended, wherein the amount of PBAT-AA accounts for 2%-20% of the mass of PBAT.

[0081] PLA and PLA-FU are core layer raw materials for forming the core layer. Specifically, PLA and PLA-FU are physically blended, wherein the amount of PLA-FU accounts for 2-20% of the mass of PLA.

[0082] The above PBAT, PBAT-AA, PLA and PLA-FU are dried in a vacuum oven at 70°C-100°C for 12h-24h. It is understood that the above four materials can be dried separately, or the core layer raw materials formed by physical blending of PLA and PLA-FU can be dried together, or the skin layer raw materials formed by physical blending of PBAT and PBAT-AA can be dried together.

[0083] Then, the PBAT / PLA sheath-core composite fiber is prepared according to the two-component spinning process, wherein the sheath extrusion temperature is 190-220°C, the core layer melt extrusion temperature is 195-220°C, the spinneret hole number is 36-100, the spinning temperature is 195-210°C, the spinning speed is 500-3000m / min, and the mass ratio of the core layer raw material to the sheath layer raw material is (3:7)-(7:3).

[0084] The embodiment of the present invention utilizes temperature-induced dynamic bond between PLA-FU and PBAT-AA molecular chains, namely Diels-Alder (DA) bond formation, to achieve long-term compatibility of PBAT / PLA two-component core-skin composite fiber. Specifically, the reversible DA bond inside PLA-FU and PBAT-AA is activated under the stimulation of a given temperature and absorbs energy from the outside, thereby achieving rapid and effective interface expansion of PBAT / PLA core-skin composite fiber during melt spinning by DA bond breaking and bonding, and then the skin and core layers of the prepared core-skin composite fiber will not phase separate over time, thereby achieving long-term expansion. D is the temperature of the DA reaction, and the approximate temperature range is 120-210°C. During the spinning process and the hot stretching process, it is a reverse reaction at this time. However, as the temperature decreases, the furan in PLA-FU and the anhydride in PBAT-AA undergo DA reaction to increase the volume, which is a positive reaction at this time. According to the above preparation method, the preparation method provided in the embodiment of the present invention only uses four raw materials, PLA-FU, PBAT-AA, PBAT and PLA, and does not require the addition of fillers and other compatibilizers, which effectively avoids the problems of low spinnability and safety of the compatibilizer materials during the fiber processing and molding process caused by the residual modifier.

[0085] In a possible embodiment, PLA can also be modified with an anhydride derivative containing an ester group to obtain anhydride-modified PLA (i.e., PLA-AA), and PBAT can be modified with a furan derivative containing an ester group to obtain furan-modified PBAT (i.e., PBAT-FU), and the preparation method will not be described in detail.

[0086] In a second aspect, the present invention provides a PBAT / PLA sheath-core composite fiber, which is prepared by the preparation method of the PBAT / PLA sheath-core composite fiber described in any one of the aforementioned embodiments.

[0087] Specifically, the PBAT / PLA sheath-core composite fiber includes a sheath layer and a core layer, wherein the sheath layer wraps around the core layer, the raw materials forming the sheath layer are composed of PBAT-AA and PBAT, and the raw materials forming the core layer are composed of PLA-FU and PLA.

[0088] In a third aspect, the present invention provides a sanitary product, which is prepared by the PBAT / PLA core-skin composite fiber described in the above embodiment. The sanitary product can be a baby diaper, a female sanitary napkin, etc.

[0089] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0090] Source of raw materials

[0091] FU1: Shenzhen Atuo Chemical Co., Ltd.;

[0092] FU2: Shenzhen Atuo Chemical Co., Ltd.;

[0093] AA1: Shanghai Hansi Chemical Co., Ltd.;

[0094] AA2: Shanghai Hansi Chemical Co., Ltd.;

[0095] PLA: Mw is 80,000-100,000, Wanhua Chemical Group Co., Ltd.

[0096] PBAT: Mw is 60,000-80,000, Wanhua Chemical Group Co., Ltd.

[0097] Example 1

[0098] This embodiment provides a method for preparing a PBAT / PLA sheath-core composite fiber (denoted as PBAT-PLA-1), comprising:

[0099] S1, formation of PLA-FU1;

[0100] FU1 and PLA resin were dried in a vacuum oven at 70°C for 12 h, and then melt-blended FU1 and PLA resin using an internal mixer to prepare PLA-FU1. The screw speed was set to 60 r / min, the blending molar ratio of FU1 to PLA was 2:8, the blending time was 10 min, and the blending temperature was 150°C to obtain PLA-FU1. The structural formula of FU1 and the structural formula and synthesis route of PLA-FU1 can be found in Figure 1 .

[0101] S2, forming PBAT-AA1;

[0102] AA1 and PBAT resin were dried in a vacuum oven at 80°C for 12h, and then melt-blended AA1 and PBAT resin using an internal mixer to prepare PBAT-AA1. The screw speed was set to 60r / min, the blending mass ratio of AA1 to PBAT was 2:8, the blending time was 10min, and the blending temperature was 150°C to obtain PBAT-AA1. The structural formula of AA1, the structural formula of PBAT-AA1, and the synthesis route can be found in Figure 2 .

[0103] S3, forming PBAT / PLA skin-core composite fiber;

[0104] PLA-FU1, PLA, PBAT-AA1 and PBAT were dried in a vacuum oven at 70°C for 12h. PBAT and PBAT-AA1 were physically blended to form the skin layer material, wherein the amount of PBAT-AA1 accounted for 5% of the mass of PBAT. PLA and PLA-FU1 were physically blended to form the core layer material, wherein the amount of PLA-FU1 accounted for 5% of the mass of PLA.

[0105] Then, PBAT / PLA sheath-core composite fibers were prepared according to the two-component spinning process. The sheath extrusion temperature was 190°C, the core melt extrusion temperature was 195°C, the spinneret hole number was 36, the spinning temperature was 195°C, and the spinning speed was 500m / min. The synthetic routes of PLA-FU1 and PBAT-AA1 are shown in Figure 3 The mass ratio of the skin layer raw material to the core layer raw material is 3:7.

[0106] Example 2

[0107] This embodiment provides a method for preparing a PBAT / PLA sheath-core composite fiber (denoted as PBAT-PLA-2), comprising:

[0108] S1, formation of PLA-FU2;

[0109] FU2 and PLA resin were dried in a vacuum oven at 85°C for 18h, and then melt blended with PLA resin using an internal mixer to prepare PLA-FU2. The screw speed was set to 90r / min, the blending molar ratio of FU2 to PLA was 5:5, the blending time was 30min, and the blending temperature was 180°C to obtain PLA-FU2. The structural formula of FU2 and the structural formula and synthesis route of PLA-FU2 can be found in Figure 1 .

[0110] S2, forming PBAT-AA2;

[0111] AA2 and PBAT resin were dried in a vacuum oven at 85°C for 18h, and then melt blended AA2 and PBAT resin using an internal mixer to prepare PBAT-AA2. The screw speed was set to 60r / min, the blending mass ratio of AA2 to PBAT was 5:5, the blending time was 30min, and the blending temperature was 180°C to obtain PBAT-AA2. The structural formula of AA2, the structural formula of PBAT-AA2, and the synthesis route can be found in Figure 2 .

[0112] S3, forming PBAT / PLA skin-core composite fiber;

[0113] PLA-FU2, PLA, PBAT-AA2 and PBAT were dried in a vacuum oven at 70°C for 18h. PBAT and PBAT-AA2 were physically blended to form the skin layer material, wherein the amount of PBAT-AA2 accounted for 5% of the mass of PBAT. PLA and PLA-FU2 were physically blended to form the core layer material, wherein the amount of PLA-FU2 accounted for 5% of the mass of PLA.

[0114] Then, PBAT / PLA sheath-core composite fibers were prepared according to the two-component spinning process. The sheath extrusion temperature was 205°C, the core melt extrusion temperature was 210°C, the spinneret hole number was 70, the spinning temperature was 200°C, and the spinning speed was 1500 m / min. The synthetic routes of PLA-FU2 and PBAT-AA2 are shown in Figure 3 The mass ratio of the skin layer raw material to the core layer raw material is 5:5.

[0115] Example 3

[0116] This embodiment provides a method for preparing a PBAT / PLA sheath-core composite fiber (denoted as PBAT-PLA-3), comprising:

[0117] S1, formation of PLA-FU2;

[0118] FU2 and PLA resin were dried in a vacuum oven at 100°C for 24 h respectively, and then melt-blended FU2 and PLA resin in an internal mixer to prepare PLA-FU2. The screw speed was set to 100 r / min, the blending molar ratio of FU2 and PLA was 5:5, the blending time was 30 min, and the blending temperature was 180°C to obtain PLA-FU2.

[0119] S2, forming PBAT-AA2;

[0120] AA2 and PBAT resin were dried in a vacuum oven at 80°C for 24h, respectively, and then melt-blended AA2 and PBAT resin using an internal mixer to prepare PBAT-AA2. The screw speed was set to 100r / min, the blending mass ratio of AA2 to PBAT was 5:5, the blending time was 30min, and the blending temperature was 210°C to obtain PBAT-AA2.

[0121] S3, forming PBAT / PLA skin-core composite fiber;

[0122] PLA-FU2, PLA, PBAT-AA2 and PBAT were dried in a vacuum oven at 100°C for 24h. PBAT and PBAT-AA2 were physically blended to form the skin layer material, wherein the amount of PBAT-AA2 accounted for 20% of the mass ratio of PBAT. PLA and PLA-FU2 were physically blended to form the core layer material, wherein the amount of PLA-FU2 accounted for 20% of the mass ratio of PLA.

[0123] Then, PBAT / PLA sheath-core composite fibers were prepared according to the two-component spinning process. The sheath extrusion temperature was 220°C, the core melt extrusion temperature was 220°C, the spinneret hole number was 3000, the spinning temperature was 210°C, and the spinning speed was 3000m / min. The mass ratio of the sheath raw material to the core raw material was 7:3.

[0124] Example 4

[0125] This embodiment provides a method for preparing a PBAT / PLA sheath-core composite fiber (denoted as PBAT-PLA-4), comprising:

[0126] S1, formation of PLA-AA1;

[0127] AA1 and PLA resin were dried in a vacuum oven at 70°C for 12 h, respectively, and then melt-blended AA1 and PLA resin using an internal mixer to prepare PLA-AA1. The screw speed was set to 60 r / min, the blending molar ratio of AA1 to PLA was 2:8, the blending time was 10 min, and the blending temperature was 150°C to obtain PLA-AA1.

[0128] S2, forming PBAT-FU1;

[0129] FU1 and PBAT resin were dried in a vacuum oven at 80°C for 12 h, respectively, and then melt-blended FU1 and PBAT resin using an internal mixer to prepare PBAT-FU1. The screw speed was set to 60 r / min, the blending mass ratio of FU1 to PBAT was 2:8, the blending time was 10 min, and the blending temperature was 150°C to obtain PBAT-FU1.

[0130] S3, forming PBAT / PLA skin-core composite fiber;

[0131] PLA-AA1, PLA, PBAT-FU1 and PBAT were dried in a vacuum oven at 70°C for 12h. PBAT and PBAT-FU1 were physically blended to form the skin layer material, wherein the amount of PBAT-FU1 accounted for 5% of the mass of PBAT. PLA and PLA-AA1 were physically blended to form the core layer material, wherein the amount of PLA-AA1 accounted for 5% of the mass of PLA.

[0132] Then, PBAT / PLA sheath-core composite fibers were prepared according to the two-component spinning process. The sheath extrusion temperature was 190°C, the core melt extrusion temperature was 195°C, the spinneret hole number was 36, the spinning temperature was 195°C, and the spinning speed was 500m / min. The mass ratio of the sheath raw material to the core raw material was 3:7.

[0133] Comparative Example 1

[0134] This comparative example provides a method for preparing a PBAT / PLA sheath-core composite fiber (denoted as PBAT-PLA), comprising:

[0135] Without modifying PBAT and PLA, the raw material of the skin layer is only PBAT, and the raw material of the core layer is only PLA. The PBAT / PLA skin-core composite fiber is prepared according to the two-component spinning process. Among them, the skin layer extrusion temperature is 190℃, the core layer melt extrusion temperature is 195℃; the number of spinneret holes is 36, the spinning temperature is 195℃, and the spinning speed is 500m / min. The mass ratio of the skin layer raw material to the core layer raw material is 3:7.

[0136] Comparative Example 2

[0137] The PBAT / PLA sheath-core composite fiber was prepared by referring to the preparation method provided in Example 1, with the only difference being that the sheath layer raw material was formed by PBAT and PBAT-AA1, and the core layer raw material was only PLA, and the other conditions and ratios were consistent with those in Example 1.

[0138] Comparative Example 3

[0139] The PBAT / PLA sheath-core composite fiber was prepared by referring to the preparation method provided in Example 1, with the only difference being that the sheath layer raw material was only PBAT, and the core layer raw materials were PLA-FU1 and PLA, and the other conditions and ratios were consistent with those in Example 1.

[0140] Test Example 1

[0141] The PBAT / PLA core-skin composite fibers of Examples 1-3 and Comparative Example 1 were tested under an optical microscope. Figure 4 .

[0142] The PBAT / PLA core-skin composite fibers of Examples 1-3 and Comparative Example 1 were tested by scanning electron microscope. Figure 5 .

[0143] according to Figure 4 and Figure 5 It can be seen that the skin-core interface of the PBAT / PLA skin-core composite fiber of Comparative Example 1 is relatively obvious, so the skin-core layer separation and skin layer rupture will occur in the subsequent thermal stretching, which directly affects the mechanical properties and subsequent use performance of the skin-core composite fiber. The PBAT / PLA skin-core composite fiber provided by the embodiment of the present invention significantly improves the interface between PBAT and PLA, and the interface compatibility between the skin and core layers is good, and there is no visible interface gap.

[0144] Test Example 2

[0145] Mechanical properties tests were performed on Examples 1 to 4 and Comparative Examples 1 to 3, and the results are shown in Table 1, Table 2, and Table 3. Test method: The mechanical properties of the fibers were tested using a fiber strength tester (model: XQ-1, Shanghai Xinxian Instrument Co., Ltd.), the test temperature was 25°C, the clamping distance was 20 mm, the tensile speed was 10 mm / min, 20 single fibers were taken from each group of samples for testing, and the average value was taken as the final test result.

[0146] Table 1 Mechanical properties after 1 day

[0147]

[0148] Table 2 Mechanical properties of fibers after 30 days

[0149]

[0150] Table 3 Mechanical properties of fibers after 180 days

[0151]

[0152] According to Table 1, in Comparative Examples 1-3, if PBAT-AA or PLA-FU is not added, the breaking strength of the PBAT / PLA core-skin composite fiber is 2.34, 2.01, and 1.99 cN / dtex, respectively, and the breaking elongation is only 30.21%, 28.6%, and 29.33%, respectively, while the PBAT / PLA core-skin composite fiber prepared by the present invention has an elongation at break of about 2 times, and its breaking strength is also improved, indicating that the DA reaction between the anhydride PBAT and the furanized PLA, and between the anhydride PLA and the furanized PBAT during the spinning process improves the compatibility of the composite fiber interface. In addition, the mechanical properties and elongation at break of the core-skin composite fibers prepared in Examples 1-4 after 30 days and 180 days are comparable to the breaking strength and elongation at break data after 1 day, indicating that the method of the present invention can achieve long-term capacity expansion of the composite fiber interface.

[0153] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a PBAT / PLA sheath-core composite fiber, characterized in that: include: S1, modifying PLA using one of an ester-containing furan derivative and an ester-containing anhydride derivative to obtain modified PLA; Modifying PBAT with the other of an ester-containing furan derivative and an ester-containing anhydride derivative to obtain a modified PBAT; S2. Using the modified PLA and the modified PBAT to perform spinning.

2. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 1, characterized in that: S1, modifying PLA with a furan derivative containing an ester group to form furanized PLA; Modifying PBAT with an anhydride derivative containing an ester group to form an anhydride PBAT; S2. Spinning the furanized PLA and the anhydride-treated PBAT.

3. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 1, characterized in that: S1, modifying PLA with an anhydride derivative containing an ester group to form anhydride PLA; The PBAT is modified with a furan derivative containing an ester group to form a furanized PBAT; S2. Spinning the anhydride-treated PLA and the furanized PBAT.

4. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 1, characterized in that: The step of modifying PLA by using one of an ester-containing furan derivative and an ester-containing acid anhydride derivative to obtain modified PLA comprises: subjecting the ester-containing furan derivative or the ester-containing acid anhydride derivative to an ester exchange reaction with the PLA; Preferably, the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA are first melt-blended; Preferably, the molar ratio of the ester-containing furan derivative or the ester-containing anhydride derivative to the PLA is (2-8): (8-2); Preferably, the conditions of the first melt blending include: blending time of 10 min-45 min, temperature of 150° C.-210° C.; further, screw speed of 60 r / min-100 r / min; Preferably, before the first melt blending, the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA are dried respectively; Preferably, the drying conditions for drying the ester-containing furan derivative or the ester-containing anhydride derivative and the PLA respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

5. The method for preparing the PBAT / PLA core-skin composite fiber according to any one of claims 1 to 4, characterized in that: At least one of the following conditions is met: (1) The structural formula of the ester-containing furan derivative is as follows: Wherein, R1 is selected from a substituted or unsubstituted aromatic group or a substituted or unsubstituted alkylene chain, and R2 is a substituted or unsubstituted alkylene chain; Preferably, R1 is selected from substituted or unsubstituted phenyl or substituted or unsubstituted C1-C10 alkylene chain, and R2 is substituted or unsubstituted C1-C10 alkylene chain; Preferably, R1 is selected from unsubstituted phenyl or unsubstituted C1-C10 alkylene chain, and R2 is an unsubstituted C1-C10 alkylene chain; More preferably, R1 is selected from unsubstituted phenyl or unsubstituted C2-C8 alkylene chain, and R2 is an unsubstituted C2-C8 alkylene chain; (2) The structural formula of the ester-containing anhydride derivative is as follows: wherein R3 is selected from a substituted or unsubstituted aromatic group or a substituted or unsubstituted alkylene chain; R3 is preferably a substituted or unsubstituted phenyl group or a substituted or unsubstituted C1-C10 alkylene chain, more preferably an unsubstituted phenyl group or an unsubstituted C1-C10 alkylene chain, and most preferably an unsubstituted phenyl group or an unsubstituted C2-C8 alkylene chain.

6. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 1, characterized in that: The step of modifying PBAT by using the other of the ester-containing furan derivative and the ester-containing acid anhydride derivative to obtain the modified PBAT comprises: subjecting the ester-containing acid anhydride derivative or the ester-containing furan derivative to an ester exchange reaction with PBAT; Preferably, the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT are subjected to a second melt blending; Preferably, the molar ratio of the ester-containing anhydride derivative or the ester-containing furan derivative to the PBAT is (2-8): (8-2); Preferably, the conditions of the second melt blending include: blending time of 10 min-45 min, temperature of 150° C.-210° C.; further, screw speed of 60 r / min-100 r / min; Preferably, before the second melt blending, the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT are dried respectively; Preferably, the conditions for drying the ester-containing anhydride derivative or the ester-containing furan derivative and the PBAT respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

7. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 1, characterized in that: The core layer raw material for forming the core layer of the PBAT / PLA core-skin composite fiber includes the modified PLA; The raw material for forming the skin layer of the PBAT / PLA skin-core composite fiber includes the modified PBAT; Spinning is performed according to a two-component spinning process; Preferably, in the two-component spinning process, the skin layer melt extrusion temperature is 190°C-220°C, and the core layer melt extrusion temperature is 195°C-220°C; the number of spinneret holes is 36-100, the spinning temperature is 195°C-210°C, and the spinning speed is 500m / min-3000m / min.

8. The method for preparing the PBAT / PLA core-skin composite fiber according to claim 7, characterized in that: The core layer raw material also includes PLA, and the amount of the modified PLA is 2%-20% of the mass of the PLA; Preferably, the skin layer raw material further comprises PBAT, and the amount of the modified PBAT is 2%-20% of the mass of the PBAT; Preferably, the mass ratio of the core layer raw material to the skin layer raw material is (3:7)-(7:3); Preferably, before spinning, the core layer raw material and the skin layer raw material are dried separately; Preferably, the conditions for drying the core layer raw material and the skin layer raw material respectively include: a temperature of 70° C.-100° C. and a time of 12 h-14 h.

9. A PBAT / PLA sheath-core composite fiber, characterized in that: The fiber is prepared by the method for preparing the PBAT / PLA sheath-core composite fiber according to any one of claims 1 to 8.

10. A sanitary product, characterized in that: Including the PBAT / PLA sheath-core composite fiber as described in claim 9.

Citation Information

Patent Citations

  • Long-acting antibacterial polyester and preparation method thereof

    CN109251309A

  • Modified cellulose fibers and preparation method and application thereof

    CN110791952A

  • Degradable tow with Y-shaped sheath-core structure for cigarette filter tip and preparation method of degradable tow

    CN112251844A

  • PBAT / PLA sheath-core composite fiber and preparation method thereof

    CN116121907A

  • Polypropylene composite material and preparation method thereof

    CN118388885A